Diagnosis and prevention of overtraining syndrome: an opinion on education strategies - Kreher JB (Dove Medical Press, 2016)
Jeffrey B Kreher Department of Orthopaedics, Division of Pediatric Orthopaedics, Massachusetts General Hospital and Massachusetts General Hospital for Children, Boston, MA, USA Abstract: Overtraining syndrome is a condition of maladapted physiology in the setting of excessive exercise without adequate rest. The exact etiology and pathogenesis are unknown and being investigated. Symptoms are multisystem in nature and often representative of underlying hormonal, immunologic, neurologic, and psychologic disturbances. Unfortunately, systematic review of the literature does not clearly direct diagnosis, management, or prevention. However, given the severity of symptoms and impairment to quality of life, prevention of overtraining syndrome should be considered by all who interact with endurance athletes. This article will provide suggestions for management of at-risk athletes despite absence of validated diagnostic tests and preventative measures. Keywords: overreaching, unexplained underperformance, burnout, muscle failure syndrome